Need Analysis of English Learning Materials for Civil Engineering Department Students - Indra Kurnia Ramadhan; Gita Mutiara Hati; Elfrida Elfrida (Journal of English Education and Teaching, 2023)
This research analyzes the Civil Engineering department students' needs for English learning materials and the need regarding the language element by students in English learning material in the civil engineering department. Populations in this research were carried out in the Department of Civil Engineering, at the University of Bengkulu. This research used descriptive quantitative research with questionnaire as the tools in collecting data and interview was carried out to find out in-depth and strengthen the questionnaire. To analyze the data, the writer involved two steps in analyzing the data collected; Give questionnaires to civil students using Google Form and then they were given 2 days to fill out and Analyze and explain the results of the list of answers from the questionnaire. The result of this research showed that the civil engineer students want to improve their English speaking skills and listening skills to communicate in their activities in the field of civil engineering where the material provided is easily understood by the students. In addition, the language element they want is more conversational. The English conversations given are more situational conversations and the texts given are more discussion texts. The last, English is important for professional needs because English is needed for everything such as the TOEFL score and confidence in their English which is one of the requirements to continue studying and to become an employee in a company.